Canadian Patent Agent Regulation Reform Pt. 1 – (In)Validity Issues Surrounding the Canadian Patent Agent Exam - Aoun, Wissam (2016)
Only registered Canadian patent agents may represent others before the Canadian Patent Office. To qualify as a registered Canadian patent agent, candidates must complete an apprenticeship followed by successfully passing the Canadian patent agent examination. This article analyzes the validity of the current Canadian patent agent exam. The analysis includes a comprehensive review of the development of the current exam, as well as a review of candidate solution papers from the most recent exams.
Keywords: Wissam Aoun